2003
DOI: 10.1186/1477-7827-1-74
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin levels in seminal plasma and sperm extracts of the domestic turkey, and the effects of cyclooxygenase inhibitors on sperm mobility

Abstract: BackgroundTurkey reproduction is by artificial insemination using pooled semen so there is interest in storing semen. Fertilizing capacity declines after six hours storage, possibly due to poor sperm mobility. Prostaglandins (PG) affect mammalian sperm motility, but avian sperm has not been widely studied. For this study, levels of PG E1, E2, and F2 alpha in turkey seminal plasma and sperm extract, and effects of cyclooxygenase (COX) inhibitors on sperm mobility were determined.MethodsSeminal Plasma and sperm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Studies on mice and turkeys showed a negative effect of coxibs on sperm parameters [47, 48]. In contrast, sperm parameters (but not morphology) improved in patients with chronic pelvic pain syndrome treated with a combination of α -blockers and coxibs [49].…”
Section: Anti-inflammatory Treatmentmentioning
confidence: 99%
“…Studies on mice and turkeys showed a negative effect of coxibs on sperm parameters [47, 48]. In contrast, sperm parameters (but not morphology) improved in patients with chronic pelvic pain syndrome treated with a combination of α -blockers and coxibs [49].…”
Section: Anti-inflammatory Treatmentmentioning
confidence: 99%
“…The inability of the male to fertilize without foam appears to be related to the absence of PGF 2α as the biological basis of sustained fertility in domestic birds is in their capacity for the sperm to reside in the SST 23 . The concentrations of PGF 2α found in the SP of turkey and rooster are reported to be 100–140 pg/ml and less than 100 pg/ml, respectively 24 25 . Those values are approximately 7 times lower than that of quail CG.…”
Section: Resultsmentioning
confidence: 99%
“…Although resveratrol was shown to be capable of preserving plasmatic membrane integrity, possibly by preventing lipid oxidative damage, it was not effective in preventing loss of motility and sperm vigor post-thawing. This behavior may be connected to antioxidant action by the resveratrol, which is a COX-1 specific inhibitor, i.e., an enzyme involved in the synthesis of E-2 series prostaglandins, which are positively correlated to sperm motility (Kennedy, Korn, & Thurston, 2003).…”
Section: Resultsmentioning
confidence: 99%